The seroprevalence of toxoplasma in healthy pregnants and evaluation of IgG aviditiy values - DURDU, BÜLENT; DURDU, BÜLENT; Mutlu, Meral (My University, 2017)
Objective: Toxoplasmosis involving all organs is a protozoal infection caused by Toxoplasma gondii. It is usually asymptomatic. Since T. gondii is very difficult to show directly or to produce on cultural media in diagnosis serological methods are preferred. But IgM antibodies which occur in the acute phase lasts very long in serum. So this leads to wrong acute infection diagnoses. Studies conducted show us that low avidity means the infection occurred in the last 3-4 months, high avidity means the infection occurred at least 6 months before. Due to this, avidity tests are used often in differentiation between acute and chronic disease. In our study we aimed to determine Toxoplasma seroprevalence and avidity values in pregnants.